Integrating sustainability into major projects : best practices and tools for project teams - McPhee, Wayne; Dias, Sabrina (John Wiley & Sons, Inc., 2020)
"With the growing need for sustainability management on large resource, infrastructure and power projects, Integrating Sustainability on Major Projects offers project teams and sustainability practitioners the practical advice, tools and resources they need to create better projects. This practitioner's guide offers extensive guidance for influencing stakeholders to integrate sustainability into project delivery. In each chapter, the authors provide invaluable sustainability management tools, such as, sample project engineering workflows, a stakeholder engagement spectrum diagram, a sample permit tracker; and a constraints mapping diagram. Major project teams are adjusting their workflows in order to integrate a focus on sustainability and corporate social responsibility. This book provides the resources major project teams need to successfully integrate sustainability into project management. Delivering the economic and social development benefits of major energy, resource, and infrastructure projects while mitigating community disruption and environmental damages is a major issue for project teams today. Sustainability management poses unique challenges for major projects like mines, pipelines, wind farms, ports and airports, offshore and onshore oil and gas, waste facilities, and other large infrastructure developments. The development of these major projects is complex and requires project teams to manage not just to budget, schedule, and quality, but also corporate social responsibility (CSR) and sustainability"--